HvFT1 polymorphism and effect—survey of barley germplasm and expression analysis - Loscos, Jorge; Igartua, Ernesto; Contreras-Moreira, Bruno; Gracia, M. Pilar; Casas, Ana M. (Frontiers in Plant Science, 2014)
Flowering time in plants is a tightly regulated process. In barley (Hordeum vulgare L.), HvFT1, ortholog of FLOWERING LOCUS T, is the main integrator of the photoperiod and vernalization signals leading to the transition from vegetative to reproductive state of the plant. This gene presents sequence polymorphisms affecting flowering time in the first intron and in the promoter. Recently, copy number variation (CNV) has been described for this gene. An allele with more than one copy was linked to higher gene expression, earlier flowering, and an overriding effect of the vernalization mechanism. This study aims at (1) surveying the distribution of HvFT1 polymorphisms across barley germplasm and (2) assessing gene expression and phenotypic effects of HvFT1 alleles. We analyzed HvFT1 CNV in 109 winter, spring, and facultative barley lines. There was more than one copy of the gene (2–5) only in spring or facultative barleys without a functional vernalization VrnH2 allele. CNV was investigated in several regions inside and around HvFT1. Two models of the gene were found: one with the same number of promoters and transcribed regions, and another with one promoter and variable number of transcribed regions. This last model was found in Nordic barleys only. Analysis of HvFT1 expression showed that association between known polymorphisms at the HvFT1 locus and the expression of the gene was highly dependent on the genetic background. Under long day conditions the earliest flowering lines carried a sensitive PpdH1 allele. Among spring cultivars with different number of copies, no clear relation was found between CNV, gene expression and flowering time. This was confirmed in a set of doubled haploid lines of a population segregating for HvFT1 CNV. Earlier flowering in the presence of several copies of HvFT1 was only seen in cultivar Tammi, which carries one promoter, suggesting a relation of gene structure with its regulation. HvCEN also affected to a large extent flowering time.